2021
DOI: 10.3390/jcm10194396
|View full text |Cite
|
Sign up to set email alerts
|

Total Lesion Glycolysis Improves Tumor Burden Evaluation and Risk Assessment at Diagnosis in Hodgkin Lymphoma

Abstract: Hodgkin lymphoma (HL) is a hematological malignancy with an excellent prognosis. However, we still need to identify those patients that could experience failed standard frontline chemotherapy. Tumor burden evaluation and standard decisions are based on Ann Arbor (AA) staging, but this approach may be insufficient in predicting outcomes. We aim to study new ways to assess tumor burden through volume-based PET parameters to improve the risk assessment of HL patients. We retrospectively analyzed 101 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…However, PET volumetric parameters are associated with prognosis, even when controlling for LMA 8,12 . Other research suggests that bPET quantitative metrics are superior to Ann Arbor staging for risk stratification 17 . Thus, bPET‐based measures of total body tumour volume provide additional prognostic information beyond Ann Arbor stage and the presence of LMA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, PET volumetric parameters are associated with prognosis, even when controlling for LMA 8,12 . Other research suggests that bPET quantitative metrics are superior to Ann Arbor staging for risk stratification 17 . Thus, bPET‐based measures of total body tumour volume provide additional prognostic information beyond Ann Arbor stage and the presence of LMA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TLG 2.5 was defined as MTV 2.5 × SUV mean of MTV 2.5 , and TLG 40% was defined as MTV 40% × SUV mean of MTV 40% . These thresholds have been used commonly for segmentation in lymphomas 7–11,13–20 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in the literature propose other clinical and PET/CT-derived markers for response to treatment [ 7 , 8 , 9 ], event-free survival [ 10 , 11 ], progression-free survival, and overall survival [ 12 , 13 , 14 ] prediction. 18 F-FDG PET/CT textural and radiomic features were also demonstrated to be useful tools in lymphoma for histological prediction, prognostic assessment, and bone marrow involvement definition.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of high-risk patients before start of treatment is still a particular challenge. In the Special Issue, Herraez et al report a retrospective survey assessing the tumor burden though volume-based PET parameters instead of using the Ann Arbor classification technique [ 5 ]. They found that a higher metabolic tumor volume and total lesion glycolysis (TLG) were significantly associated with a higher incidence of stages III–IV, B-symptoms, hypoalbuminemia, and lymphopenia, and a higher international prognostic score.…”
mentioning
confidence: 99%